2013
DOI: 10.1101/gad.198630.112
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulated mTORC1 renders cells critically dependent on desaturated lipids for survival under tumor-like stress

Abstract: Solid tumors exhibit heterogeneous microenvironments, often characterized by limiting concentrations of oxygen (O2), glucose, and other nutrients. How oncogenic mutations alter stress response pathways, metabolism, and cell survival in the face of these challenges is incompletely understood. Here we report that constitutive mammalian target of rapamycin complex 1 (mTORC1) activity renders hypoxic cells dependent on exogenous desaturated lipids, as levels of de novo synthesized unsaturated fatty acids are reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
220
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 181 publications
(256 citation statements)
references
References 44 publications
8
220
1
2
Order By: Relevance
“…Albumin is a carrier protein for lipids (52), and thus, the scavenging of albumin also involves the scavenging of lipids. It was recently reported that constitutive mTORC1 activity renders hypoxic cells dependent on exogenous desaturated lipids for survival (53). Although this study did not connect the need for desaturated lipids and the dependence of mTOR on PA, it did provide further evidence for a lipid dependence of mTOR and potentially a dependence on desaturated lipids.…”
Section: Compensatory Production Of Pa In Response To Metabolic Stresmentioning
confidence: 49%
“…Albumin is a carrier protein for lipids (52), and thus, the scavenging of albumin also involves the scavenging of lipids. It was recently reported that constitutive mTORC1 activity renders hypoxic cells dependent on exogenous desaturated lipids for survival (53). Although this study did not connect the need for desaturated lipids and the dependence of mTOR on PA, it did provide further evidence for a lipid dependence of mTOR and potentially a dependence on desaturated lipids.…”
Section: Compensatory Production Of Pa In Response To Metabolic Stresmentioning
confidence: 49%
“…35); and (c) previous work demonstrated that synthesizing or scavenging unsaturated lipids is critical to maintaining cell viability in multiple transformed cell types, especially encountering elevated protein synthesis (36,37). Decreased SCD1 protein accumulation upon IRE1α RNase inhibition was confirmed in multiple cell lines ( Figure 5C and Supplemental Figure 5, D and E).…”
Section: B-i09 Suppresses Growth and Induces Apoptosis In Human And Mmentioning
confidence: 50%
“…However, to maintain ER homeostasis in cells with oncogene-driven protein synthesis, ER lipid membrane biogenesis must also be regulated to accommodate elevated protein load. For example, our previous studies revealed an essential role for unsaturated lipids in maintaining ER homeostasis and viability in cells with constitutive mTORC1 activity (48). The relationship between the UPR and ER lipid homeostasis is underscored by data demonstrating mutant IRE1α and PERK proteins lacking the ability to sense unfolded proteins retain their responsiveness to increased lipid saturation (49) and showing that SCD1 inhibition initiates ER stress in multiple conditions (50,51).…”
Section: Discussionmentioning
confidence: 95%
“…mTORC1 plays a central role in the control of cell growth, and evidence indicate that the activation of SREBPdependent lipid synthesis is one essential downstream factor in its promotion of growth. 9,10 Recent studies have further suggested that, in parallel to its induction of protein synthesis, mTORC1 must also activate SREBP and de novo lipid synthesis in order to prevent ER stress, 36,37 which results from the accumulation of misfolded proteins in the ER. The essential nature of SREBP in the context of mTORC1 activation underlies a need to balance an increase in protein load in the ER and elsewhere with the expansion of ER and other cellular membranes through de novo lipid synthesis.…”
Section: Nrf1 and Its Physiological Activation By Mtorc1 And Srebp1mentioning
confidence: 99%